Who Cares? Care and the Ethical Self - Lanoix, Monique (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2015)
Over three decades ago, Carol Gilligan’s seminal book In a Different Voice provided feminist theorists with a powerful new approach to address the shortcomings of traditional moral theories. With a focus on concrete situations, an ethics of care can attend to the specifics of moral dilemmas that might otherwise be glossed over. As feminist reflection on moral and political philosophizing has progressed, another challenge has emerged. Recent feminist scholarship proposes non-ideal theories as preferable action-guiding theories. In this paper, I examine Kittay’s call for a version of care ethics as a naturalized ethics that comes from lived experience, in order to draw out the salient characteristics of the caring agent. This allows me to show how Kittay’s key assertion that “we are all some mother’s child” resonates with Ricoeur’s framing of self-esteem, which is, in turn, anchored on a notion of solicitude. Secondly, I make the case that care ethics can benefit from Ricoeur’s little ethics as it helps buttress the goal of good caring practices. Finally, care ethics, with its emphasis on the universality of care needs, helps to strengthen the central role of solicitude for the political sphere.